Coping with Relationship Loss by Denial and Acceptance: Direct and Indirect Associations with Engagement in Post-Relationship Pursuit Behaviors Among College Men and Women - Dardis, Christina M. (Journal of family violence, 2023)
PurposePrior research has indicated that several theories might be incorporated to understand perpetration of post-relationship pursuit behaviors (PPBs). However, difficulties coping with relationship loss have not been directly assessed as potential predictors of PPB perpetration, despite their potential relevance. Thus, the present study tests an integrative model to assess whether acceptance or denial-based coping with relationship loss are associated with minor PPBs (e.g., following, excessive contact) and severe PPBs (e.g., aggression) when including prior theoretically relevant variables, such as prior relationship violence (part of coercive control theory) and break-up related distress and rumination (relational goal pursuit theory). Potential differences in predictors of in-person and cyber PPBs are explored, as are moderating effects of gender.MethodN= 821 undergraduates (59.4% women) who experienced a break-up within the past two years completed measures related to in-person and severe PPBs, coping strategies, prior relationship violence, and relational goal pursuit constructs.ResultsCoping by acceptance was associated with reductions in minor PPBs among men (but not women), whereas coping by denial was associated with increases in minor and severe PPBs across genders, through direct and indirect paths. Supporting prior research, relational goal pursuit was related only to minor PPBs, whereas prior relationship violence was associated with all PPBs, particularly among men. There were few differences in predictors of in-person and cyber PPBs.ConclusionDenial over relationship loss may serve as a risk factor for PPB engagement, whereas coping by acceptance may serve a more limited protective role. Additional risk factors remain important to study in future research.